Estimating the risk of financial distress using a multi-layered governance criterion: Insights from Middle Eastern and North African banks - Ali Meftah Gerged; Mohamed Marie; Israa Elbendary (Journal of Risk and Financial Management, 2022)
In this study, we explored the association of bank-level governance and state-level governance with the likelihood of banks' financial distress in developing economies. Using a panel data sample of 954 bank-year observations of 106 conventional banks across 14 Middle Eastern and North African (MENA) countries from 2010 to 2018, we found that bank governance arrangements seemed to be negatively attributed to the probability of financial distress. We also found that the relationship of political stability with financial distress prospects is-contrary to our expectation-insignificant, whereas government effectiveness negatively influences the likelihood of financial distress. Our empirical evidence offers practical implications for bank managers, regulators, and credit rating agencies, and suggests several future research avenues that can build on our findings.
Keywords: G01; G30; G41; 650; corporate governance; banking institutions; country-level governance; financial distress likelihood; Middle East and North Africa